Rotten! : vultures, beetles, slime and nature's other decomposers - Sanchez, Anita, 1956- (Houghton Mifflin Harcourt, 2019)
Decomposition is necessary part of the life cycle, and readers will learn about the players in the process-including the sights, the textures, and the smells.